Flexing, the Fake Rich Phenomenon - Nanang Qosim Yusuf; Dewi Umronih Yusuf (Journal of Social Research, 2024)
Of course everyone wants to be rich and to achieve it, but fake rich is a phenomenon that is now unconsciously holding young people hostage, this term is more appropriate is "flexing", there are several motives that will be discussed in this journal and what characteristics are included in a lie. The term Crazy Rich has been familiar for several months, they even got a place in netizens because they are like the British hero 'Robin Hood', distributing money to the poor from corruptors, but their musk was finally exposed one by one, even some of them had to face the police because of this, the opposite situation is "financially impoverished by the police" becausethe situation is not like the story of Robin Hood's hero but they get the money from the results of "money game (cheating)" its members are lured by bonuses of billions, in other words, more and more people become its members, more and more will fail and failure is money for them. This journal also provides tips on how we should respond it in this VUCA era.